The Russia-Ukraine war’s "Armageddon" threat: A call to action for nuclear disarmament - E. Archibong, James; Nabiebu, Miebaka (Edelweiss Applied Science and Technology, 2024)
The first atomic weapon was constructed in 1945 as a result of the discovery of nuclear fission. In the Japanese cities of Hiroshima and Nagasaki during World War II, the US first exploded the weapon in 1945. Since then, more than 12,000 different kinds of nuclear weapons and advanced delivery systems have been obtained by nine other countries. Despite efforts to outlaw and eliminate nuclear weapons, Russia has made it known that it intends to use them in the conflict it is currently engaged in with Ukraine, which began in February 2022. This study looks at the Russian menace that has frightened the world and brought to mind the tragic US nuclear attacks and the ensuing massive destruction of the environment, material resources, and human lives. Fears of a nuclear war and destruction have increased due to the potential for nuclear reprisal from the West. According to this research, there is a serious risk to human survival from the presence of nuclear weapons. It also concludes that there is a genuine risk that nuclear weapons will be used in today’s military conflicts. The paper suggests that, by the Treaty on the Prohibition of Nuclear Weapons, which went into effect on January 22, 2021, the current stockpile of nuclear weapons be immediately disarmed and destroyed.